Organic amine absorbent regeneration catalyst for carbon capture and preparation method thereof
By developing an organic amine absorber regeneration catalyst with a highly graphitized structure and multi-stage pores, the problems of high energy consumption and catalyst stability of the traditional alcohol amine absorption method are solved, and the carbon capture effect with high efficiency and low energy consumption is achieved.
Patent Information
- Application Number
- CN202411883047.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-18
AI Technical Summary
The traditional alcohol amine absorption method has high energy consumption problems in carbon capture concentration, and solid acid catalysts are prone to oxidation and poisoning under extreme conditions, affecting circulation stability.
An organic amine absorber regeneration catalyst for carbon capture, including highly graphitized carbon layer support and atomically dispersed metal elements coordinated with nitrogen elements, with a multi-stage pore structure and high specific surface area. The catalyst is produced by a preparation method, including the preparation of metal organic frame materials, heat treatment and mixed grinding with nitrogen-containing organic compounds.
The carbon capture CO2 desorption kinetics are improved, the energy consumption and operating costs of the CO2 desorption process are reduced, the high reactivity and stability are achieved, and the ability to withstand strong acid and strong alkali etching is improved, which is the durability of the catalyst.
Smart Images

Figure CN119633873A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of carbon capture, and in particular to an organic amine absorbent regeneration catalyst for carbon capture and a preparation method thereof. Background Art
[0002] Coal-fired flue gas is the main source of carbon emissions. In order to achieve the goal of "carbon peak and carbon neutrality", the development of pollution reduction and carbon reduction technologies and green electricity is particularly critical. At present, alcohol amine absorption methods such as MEA are widely used for post-combustion carbon capture of coal-fired flue gas due to their rapid absorption, mature technology and compatibility with existing technology systems. However, the strong bond between the N atoms in alcohol amines and CO2, and the difficulty of traditional technology in accurately controlling the proton migration process in an alkaline environment, lead to a high CO2 desorption temperature (usually between 110 and 130 ° C). Therefore, the energy consumption cost greatly limits the technological progress and further promotion of the alcohol amine absorption method.
[0003] Given the high energy consumption of the alcoholamine absorption method, developing highly active solid acid materials to improve the mass transfer, heat transfer, and kinetics of the CO2 desorption process is an effective approach to promoting the development of low-energy carbon capture technologies. Regarding solid-acid-catalyzed CO2 desorption processes, patent CN110681413A proposes a method for preparing a nano-FeZr@composite molecular sieve catalyst for the desorption of CO2-rich amine solutions, and patent CN110681410A proposes a method for preparing an SBA-15 molecular sieve-based supported catalyst for the desorption of CO2-rich amine solutions. These results demonstrate that the addition of solid acid can act as acidic sites, enhancing CO2 desorption efficiency. However, the composite catalysts studied in these methods utilize a metal oxide loaded onto a molecular sieve support and enhanced by sulfuric acid acidification. Alcoholamine carbon capture systems are subject to extremely harsh conditions, such as high temperature and strong oxidizing properties. Furthermore, organic amines and metals easily form stable metal-N coordination structures, leading to catalyst oxidation, poisoning, and leaching, which severely impacts the catalyst's cyclic stability.
[0004] In view of this, the present invention is proposed. Summary of the Invention
[0005] The purpose of the present invention is to provide an organic amine absorbent regeneration catalyst for carbon capture and a preparation method thereof. The catalyst has high activity and high stability, can improve the CO2 desorption kinetics of carbon capture, thereby reducing the energy consumption of the CO2 desorption process and the carbon capture operating cost, thereby achieving the purpose of energy conservation and emission reduction. The preparation method is simple and easy, the raw materials are easy to obtain, and it is suitable for large-scale production.
[0006] The first aspect of the present invention provides an organic amine absorbent regeneration catalyst for carbon capture, comprising: a carbon layer support and metal elements and nitrogen elements doped on its surface; the carbon layer support has a highly graphitized structure, and the ID / IG ratio of the Raman spectrum is less than 2; the metal elements are in an atomic-level dispersed state on the surface of the carbon layer support; the metal elements are coordinated with the nitrogen elements and are jointly loaded on the surface of the carbon layer support.
[0007] In one embodiment, the ID / IG ratio of the Raman spectrum is 1.55.
[0008] Preferably, the catalyst has a multi-level pore structure (mainly mesopores) with a specific surface area of 200m 2 / g or above.
[0009] Preferably, the metal element is a transition metal, and the transition metal includes any one or more of iron, zirconium, manganese, cobalt, nickel and copper.
[0010] Preferably, the metal element, nitrogen element and carbon element exist in the form of metal-nitrogen-carbon coordination, and the molar ratio of the nitrogen element to the metal element is (4-6):1.
[0011] Preferably, the metal element accounts for 0.5-1% of the total mass of the catalyst.
[0012] A second aspect of the present invention provides a method for preparing an organic amine absorbent regeneration catalyst for carbon capture, comprising the following steps:
[0013] S1. Preparation of metal organic framework materials;
[0014] S2, heat-treating the metal organic framework material prepared in step S1 to obtain a nitrogen-doped carbon material;
[0015] S3, immersing the carbon material obtained in step S2 in a metal precursor solution to obtain a metal-based carbon material precursor;
[0016] S4, heat-treating the metal-based carbon material precursor obtained in step S3 to obtain a material having a metal-nitrogen-carbon coordination structure;
[0017] S5. Mix and grind the metal-nitrogen-carbon coordination structure material obtained in step S4 with the nitrogen-containing organic compound, and then perform heat treatment to obtain the catalyst.
[0018] Preferably, the metal organic framework material is a zinc-based metal organic framework material.
[0019] Preferably, the nitrogen-containing organic compound includes any one or more of 1,10-phenanthroline, dimethylimidazole, and melamine, and more preferably 1,10-phenanthroline.
[0020] Preferably, the mass ratio of the material having the metal-nitrogen-carbon coordination structure to the nitrogen-containing organic compound is 1:(0.5-2), more preferably 1:1.
[0021] Preferably, the metal precursor solution includes any one or more of chlorides, nitrates, and sulfates of iron, zirconium, manganese, cobalt, nickel, and copper, such as ferric chloride, ferric nitrate, ferric sulfate, zirconium chloride, manganese nitrate, cobalt chloride, nickel chloride, and copper sulfate.
[0022] Preferably, the temperature range of the heat treatment is controlled at 900-1000° C.; the time of the heat treatment is 1-2 hours; and the heat treatment is performed under a nitrogen or argon atmosphere.
[0023] The third aspect of the present invention provides the use of the organic amine absorbent regeneration catalyst for carbon capture. Specifically, the catalyst and the organic amine absorbent are used for carbon capture.
[0024] Preferably, the mass ratio of the catalyst to the organic amine absorbent is (0.01-1):100, more preferably 0.01:100.
[0025] Preferably, the organic amine absorbent is ethanolamine.
[0026] Specifically, the absorption process uses a 30% by mass ethanolamine solution to absorb CO2 at 40°C, the catalyst dosage is 0.1wt% of the ethanolamine solution, and CO2 gas with a purity of 99.99% is introduced at a CO2 gas flow rate of 150-250 ml / min.
[0027] Specifically, the regeneration temperature of the desorption process is about 80° C., and a constant temperature oil bath is used to heat the absorption saturated solution.
[0028] The present invention has at least the following beneficial effects:
[0029] (1) The metal active material in the catalyst provided by the present invention is in the carbon-nitrogen protective layer, the active sites are dispersed, and there is a stable protective layer around the active sites, which has higher reaction activity and stability than supported catalysts.
[0030] (2) The catalyst provided by the present invention has a multi-level pore structure and a high specific surface area, which facilitates the diffusion of reactants and can further improve the reaction activity of the catalyst.
[0031] (3) The catalyst provided by the present invention has a highly graphitized structure. A higher degree of graphitization can effectively improve the stability of the material, thereby further improving the stability and durability of the catalyst. The catalyst provided by the present invention can not only accelerate the CO2 desorption performance in the organic amine absorbent, but also withstand strong acid and strong alkali etching, effectively improving the durability of the catalyst.
[0032] (4) Compared with most metal oxide materials that have been studied and prepared, the catalyst provided by the present invention has a stable nanostructure with a particle size of about 200 nanometers. It can be used as a nanofluid or as a monolithic filler in existing CO2 capture devices, which can effectively improve the flue gas treatment efficiency and alleviate the secondary aerosol pollution and equipment corrosion problems caused by the volatilization of the absorbent at high temperatures.
[0033] (5) The catalyst provided by the present invention can be used as a heterogeneous catalyst to accelerate the absorption efficiency of CO2 by organic amine absorbent. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the specific embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0035] Figure 1 This is the high-resolution transmission microscopy result of the Phen-Fe-NC catalyst in Example 4 of the present invention.
[0036] Figure 2 This is the spherical aberration electron microscopy result of the Phen-Fe-NC catalyst in Example 4 of the present invention.
[0037] Figure 3 These are the X-ray diffraction results corresponding to the Fe-NC and Phen-Fe-NC catalysts in Examples 3 and 4 of the present invention.
[0038] Figure 4 These are the Raman results corresponding to the Fe-NC and Phen-Fe-NC catalysts in Examples 3 and 4 of the present invention.
[0039] Figure 5 These are the catalytic desorption activity results of the catalysts in Examples 1 to 4 of the present invention.
[0040] Figure 6 These are the stability test results of the catalysts of Examples 1 to 4 of the present invention. DETAILED DESCRIPTION
[0041] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the present application belongs.
[0042] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular also includes the plural. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this specification, they indicate the presence of features, steps, operations, devices, components and / or combinations thereof.
[0043] The following will clearly and completely describe the technical solutions of the present invention in conjunction with the embodiments. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.
[0044] Example 1
[0045] This embodiment provides a method for preparing an organic amine absorbent regeneration catalyst (Co-NC) for carbon capture, comprising the following steps:
[0046] S1. Dissolve 20 g of dimethylimidazole in 50 mL of methanol to obtain solution A; dissolve 5 g of zinc nitrate in 50 mL of methanol to obtain solution B; pour solution A into solution B with stirring at 300 rpm, and continue stirring for 24 hours; separate the solid by centrifugation, and vacuum dry it at 60°C for 24 hours to obtain a white solid product, i.e., zinc-based metal-organic framework ZIF-8.
[0047] S2. Place the white solid product in a tube furnace in a nitrogen or argon atmosphere, heat from room temperature to 950°C at a heating rate of 5°C / min, and hold for 2 hours to obtain a black nitrogen-doped carbon material.
[0048] S3. Dissolve 0.2 g of cobalt chloride in 100 mL of water until fully dissolved. Add 10 g of nitrogen-doped carbon material to the cobalt chloride solution, stir thoroughly for 6 h, then centrifuge and dry at 100° C. for 6 h to obtain a metal-based carbon material precursor, i.e., a composite of cobalt and nitrogen-doped carbon material.
[0049] S4. The metal-based carbon material precursor was calcined at 950° C. for 2 hours at a heating rate of 5° C. / min under a nitrogen atmosphere by thermal cracking to obtain a black Co-NC catalyst powder.
[0050] Example 2
[0051] This embodiment provides a method for preparing an organic amine absorbent regeneration catalyst (Ni-NC) for carbon capture. The difference from Example 1 is that the cobalt chloride in Example 1 is replaced by nickel chloride. The other steps and amounts are the same as those in Example 1.
[0052] Example 3
[0053] This embodiment provides a method for preparing an organic amine absorbent regeneration catalyst (Fe-NC) for carbon capture. The difference from Example 1 is that the cobalt chloride in Example 1 is replaced by ferric chloride with a mass of 0.25 g. The other steps and amounts are the same as those in Example 1.
[0054] Example 4
[0055] This embodiment provides a method for preparing an organic amine absorbent regeneration catalyst (Phen-Fe-NC) for carbon capture, comprising the following steps:
[0056] Steps S1-S4 are consistent with those in Example 3.
[0057] S5. The Fe-NC catalyst obtained in step S4 and 1,10-phenanthroline were mixed and ground in a mass ratio of 1:1. The obtained uniformly mixed solid was calcined at 950° C. for 2 hours at a heating rate of 5° C. / min under a nitrogen atmosphere to obtain a black Phen-Fe-NC catalyst powder.
[0058] Test Example 1 Electron Microscope Test
[0059] The Phen-Fe-NC catalyst prepared in Example 4 was tested by high-resolution transmission electron microscopy. Figure 1 As shown. Figure 1 It can be seen that the Phen-Fe-NC catalyst has no obvious crystallinity and is mainly an amorphous structure.
[0060] The Phen-Fe-NC catalyst prepared in Example 4 was tested by spherical aberration electron microscopy. The results are as follows: Figure 2 As shown. Figure 2 It can be seen that the metal elements are dispersed at the atomic level on the surface of the carbon layer carrier.
[0061] Test Example 2 X-ray diffraction test
[0062] The Fe-NC and Phen-Fe-NC catalysts prepared in Examples 3 and 4 were subjected to X-ray diffraction tests. The results are as follows: Figure 3 As shown. Figure 3It can be seen that no crystallization of the metal elements is observed, which further indicates that the metal elements have a highly dispersed single atomic form on the surface of the carbon layer support.
[0063] Test Example 3 Raman Test
[0064] The Fe-NC and Phen-Fe-NC catalysts prepared in Examples 3 and 4 were subjected to Raman testing. Figure 4 As shown. Figure 4 It can be seen that the carbon element is primarily represented by the defective D peak signal. After the Phen-Fe-NC catalyst of Example 4 was mixed with 1,10-phenanthroline and pyrolyzed in Example 3, the graphite phase carbon signal (G peak) was enhanced. The signal intensity ID / IG decreased from 2.08 (Fe-NC) to 1.55 (Phen-Fe-NC). This indicates that the Phen-Fe-NC catalyst of Example 4 has a more stable graphite phase structure.
[0065] Test Example 4 Catalytic Desorption Activity Test
[0066] Absorption process: CO2 absorption experiments were conducted at 40°C. Each test used 80 g of a 30% ethanolamine solution (80 g mass). The catalyst dosage was 0.1 wt%. 99.99% pure CO2 gas was introduced at a flow rate of 200 ml / min for 2 hours.
[0067] Desorption process: The saturated solution was heated in a constant-temperature oil bath, with a regeneration temperature of approximately 80°C. The CO2 concentration in the reactor outlet gas was measured using an online flue gas analyzer. The total amount of CO2 desorbed by the solvent was measured using an online CO2 concentration monitor. To control solution evaporation, a condenser reflux device was installed at the gas outlet.
[0068] The catalysts prepared in Examples 1 to 4 were used to test the catalytic desorption activity using the above method. The test results are as follows: Figure 5 As shown, compared with non-catalytic conditions, the maximum desorption rate of the Co-NC catalyst prepared in Example 1 reached 2.71 mmol / min, which was 23% higher than that of the control experiment without catalyst; the maximum desorption rate of the Ni-NC catalyst prepared in Example 2 reached 3.11 mmol / min, which was 41% higher than that of the control experiment without catalyst; the maximum desorption rate of the Fe-NC catalyst prepared in Example 3 reached 2.59 mmol / min, which was 17% higher than that of the control experiment without catalyst; the maximum desorption rate of the Phen-Fe-NC catalyst prepared in Example 4 reached 3.30 mmol / min, which was 49% higher than that of the control experiment without catalyst.
[0069] It can be seen that the catalysts prepared in Examples 1 to 4 can increase the CO2 desorption rate by 17-49%, and have good catalytic activity, especially the Phen-Fe-NC catalyst in Example 4 has the highest improvement on the CO2 desorption rate.
[0070] Test Example 5: Stability Test
[0071] The catalysts prepared in Examples 1 to 4 were subjected to a cyclic stability test. The specific test method was as follows: 80g of a 30% ethanolamine solution and 0.1wt% of the catalyst were added to a hydrothermal reactor, which was sealed and kept in an oven at 100°C for 2 weeks. After the reaction was completed, the mixture was naturally cooled to room temperature. Centrifugation was performed, and the supernatant was collected and the metal ion concentration in the solution was tested. The results were as follows: Figure 6 As shown. Figure 6 It can be seen that the Co-NC catalyst prepared in Example 1 contained 107.7 ppb of Co metal ions after being in the carbon capture solution for two weeks; the Ni-NC catalyst prepared in Example 2 contained 243.3 ppb of Ni metal ions after being in the carbon capture solution for two weeks; the Fe-NC catalyst prepared in Example 3 contained 1140.9 ppb of Fe metal ions after being in the carbon capture solution for two weeks; and the Phen-Fe-NC catalyst prepared in Example 4 contained 69.0 ppb of Fe metal ions after being in the carbon capture solution for two weeks at 100°C, which is much lower than the catalysts prepared in Examples 1 to 3. These results demonstrate that nitrogen-containing organic compounds such as 1,10-phenanthroline can fill material defects, reduce their degree, increase the graphite phase of the material, and form a stable graphite-phase carbon support, ultimately resulting in a catalytic desorption material with both high activity and high stability.
[0072] In summary, the metal active substances in the catalyst of the present invention are in the carbon-nitrogen protective layer, the active sites are dispersed, and there is a stable protective layer around the active sites, which has higher reaction activity and stability; it has a highly graphitized structure, which can improve the stability and durability of the catalyst; it has a multi-level pore structure and a high specific surface area, which is conducive to the diffusion of reactants and helps to improve the reaction activity of the catalyst; it can also withstand strong acid and strong alkali etching, thereby improving the durability of the catalyst; the regenerated catalyst of the present invention can greatly improve the CO2 desorption performance of the organic amine absorbent.
[0073] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the above embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. An organic amine absorbent regeneration catalyst for carbon capture, characterized in that: include: Carbon layer support and metal elements and nitrogen elements doped on its surface; The carbon layer carrier has a highly graphitized structure, and the ID / IG ratio of the Raman spectrum is less than 2; The metal element is in an atomic-level dispersed state on the surface of the carbon layer carrier; the metal element is coordinated with the nitrogen element and is jointly loaded on the surface of the carbon layer carrier.
2. The organic amine absorbent regeneration catalyst for carbon capture according to claim 1, characterized in that: The metal element, nitrogen element and carbon element exist in a metal-nitrogen-carbon coordination form, and the molar ratio of the nitrogen element to the metal element is (4-6):
1.
3. The organic amine absorbent regeneration catalyst for carbon capture according to claim 1, characterized in that: The metal element is a transition metal, and the transition metal includes any one or more of iron, zirconium, manganese, cobalt, nickel and copper.
4. The organic amine absorbent regeneration catalyst for carbon capture according to claim 1, characterized in that: The catalyst has a multi-level pore structure with a specific surface area of 200m 2 / g or above.
5. The method for preparing an organic amine absorbent regeneration catalyst for carbon capture according to any one of claims 1 to 4, characterized in that: The steps include: S1. Preparation of metal organic framework materials; S2, subjecting the metal organic framework material prepared in step S1 to heat treatment to obtain a nitrogen-doped carbon material; S3, immersing the carbon material obtained in step S2 in a metal precursor solution to obtain a metal-based carbon material precursor; S4, heat-treating the metal-based carbon material precursor obtained in step S3 to obtain a material having a metal-nitrogen-carbon coordination structure; S5, mixing and grinding the material with the metal-nitrogen-carbon coordination structure obtained in step S4 and the nitrogen-containing organic compound, and then heat-treating to obtain the catalyst.
6. The method for preparing an organic amine absorbent regeneration catalyst for carbon capture according to claim 5, characterized in that: The metal organic framework material is a zinc-based metal organic framework material.
7. The method for preparing an organic amine absorbent regeneration catalyst for carbon capture according to claim 5, characterized in that: The nitrogen-containing organic compound includes any one or more of 1,10-phenanthroline, dimethylimidazole and melamine.
8. The method for preparing an organic amine absorbent regeneration catalyst for carbon capture according to claim 5, characterized in that: The metal precursor solution includes any one or more of chlorides, nitrates and sulfates of iron, zirconium, manganese, cobalt, nickel and copper.
9. The method for preparing an organic amine absorbent regeneration catalyst for carbon capture according to claim 5, characterized in that: The temperature range of the heat treatment is controlled at 900-1000°C.
10. The use of an organic amine absorbent regeneration catalyst for carbon capture according to any one of claims 1 to 4, characterized in that: The catalyst and the organic amine absorbent are used for carbon capture.
Citation Information
Patent Citations
Preparation method of SBA-15 molecular sieve-based supported catalyst for desorption of CO2-rich amine solution
CN110681410A
Preparation method of nano FeZr@composite molecular sieve catalyst for desorption of CO2-rich amine solution
CN110681413A